Co-creating corporate brand identity with online brand communities: a managerial perspective - Essamri, A.; McKechnie, S.; Winklhofer, H. (Elsevier, 2018)
Contemporary branding literature views brand identity as socially constructed through complex interactions between multiple stakeholders. Despite extant work on how brand communities and individuals contribute towards brand identity formation, our understanding of management-led processes constituting part of the wider process of a socially constructed brand identity is still under-developed. Drawing on in-depth interviews with senior executives of a luxury automotive company and a netnography of its online brand community, we develop a process model of corporate brand identity co-creation, comprising three management-led processes: ‘nurturing brand passion’, ‘bridging’ corporate brand identity meanings and ‘partnering’, and associated activities through which management contribute to the wider process of corporate brand identity formation with community members and other stakeholders. By highlighting the interlinked and recursive nature of these processes and activities in the resulting model, the study offers a deeper understanding of the ways in which management are involved in co-creating corporate brand identity.